0
$\begingroup$

$$\left(\frac{5}{5}\right)^n \cdot \left(\frac{9}{10}\right)^n = \left(\frac{1}{5}\right)^n \cdot \left(5 \cdot \frac{9}{10}\right)^n $$

I would like for someone to explain in laymen's terms how to use the following algebraic manipulation function: the left bracket has been multiplied by $5^{-1}$, and the right bracket has been multiplied by $5$. Can someone please explain how this works ?

thankyou

$\endgroup$
  • 2
    $\begingroup$ Keep in mind that $(a/b)^n=a^n/b^n$. Apply this and it will be clearer. $\endgroup$ – MathematicianByMistake Jan 22 '16 at 21:11
  • 1
    $\begingroup$ $$\left(\frac{5}{5}\right)^n*\left(\frac{9}{10}\right)^n=\frac{5^n}{5^n}*\frac{9^n}{10^n}=\frac{1}{5^n}*\frac{5^n*9^n}{10^n}=\left(\frac{1}{5}\right)^n * \left(\frac{5*9}{10}\right)^n$$ $\endgroup$ – Mufasa Jan 22 '16 at 21:11
  • 1
    $\begingroup$ If you prefer, you can think of this as a "multiplication by one." You may always multiply by one or add zero and it does not change the value. Here, we have $ab = ab \cdot \frac{c}{c} = (ac)\cdot (\frac{b}{c})$ $\endgroup$ – JMoravitz Jan 22 '16 at 21:15
  • $\begingroup$ This has certainly cleared things up, thank you for your help :) $\endgroup$ – Flewitt Connor Jan 22 '16 at 21:19
1
$\begingroup$

$$\begin{align}(5/5)^n \times (9/10)^n &= (5^n/5^n) \times (9/10)^n \\&= 5^n\times(1/5)^n \times (9/10)^n \\&= (1/5)^n \times (5\times9/10)^n\end{align}$$

Because $(a/b)^n=a^n/b^n$ and $a^n\times b^n=(a\times b)^n$.

$\endgroup$
  • $\begingroup$ Got it ! Thanks very much, I see now that 5/5 = 1 = 5*1/5....and the 5 can be used to multiply the 9 inside the bracket, the 1/5 part remains the same :) $\endgroup$ – Flewitt Connor Jan 22 '16 at 21:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.